Republic of Korea : studies on the social dimensions of globalization - Torres, Raymond (ILO GenevaCH, 2001)
Seeks to help improve understanding of the effects of the gradual and selective approach to globalization in terms of wages, employment and social progress. Highlights certain unsustainable elements of the process, which might have contributes to the financial crisis.